The Role of Teachers in the Formation of Students' Entrepreneurial Character at SMK Negeri 1 Polewali - Isgunandar, Isgunandar; Masdar, Patima; Nasrullah, Muh (Pinisi Journal of Education and Management, 2023)
The role of teachers in forming the entrepreneurial character of class x students at SMK Negeri 1 Polewali. This research aims to determine the role of teachers in forming the entrepreneurial character of class x students at SMK Negeri 1 Polewali. This research is quantitative research that shows cause and effect. The sample in this study was 51 students at Polewali State Vocational School 1 using a simple random sampling technique. The data collection techniques used are observation, questionnaires, and documentation. The data analysis techniques used in this research are descriptive data analysis and inferential statistical analysis. The research results show that the teacher's role is in the "Very good" category with 4 indicators, namely educator, mentor, teacher, and motivator. Meanwhile, the entrepreneurial character formation of class X students at SMK Negeri 1 Polewali is in the "Very good" category with 3 indicators, namely optimistic, responsible, and paying attention to quality. Based on the results of simple linear regression analysis, it can be concluded that there is a positive and significant influence on the role of teachers in the formation of the entrepreneurial character of class X students at SMK Negeri 1 Polewali